Oxidative stress in coronary artery bypass surgery - Dias,Amaury Edgardo Mont’Serrat Ávila Souza (2015)
Abstract Objective: The aim of this prospective study was to assess the dynamics of oxidative stress during coronary artery bypass surgery with cardiopulmonary bypass. Methods: Sixteen patients undergoing coronary artery bypass grafting were enrolled. Blood samples were collected from the systemic circulation during anesthesia induction (radial artery - A1), the systemic venous return (B1 and B2) four minutes after removal of the aortic cross-clamping, of the coronary sinus (CS1 and CS2) four minutes after removal of the aortic cross-clamping and the systemic circulation four minutes after completion of cardiopulmonary bypass (radial artery - A2). The marker of oxidative stress, malondialdehyde, was measured using spectrophotometry. Results: The mean values of malondialdehyde were (ng/dl): A1 (265.1), B1 (490.0), CS1 (527.0), B2 (599.6), CS2 (685.0) and A2 (527.2). Comparisons between A1/B1, A1/CS1, A1/B2, A1/CS2, A1/A2 were significant, with ascending values (P<0.05). Comparisons between the measurements of the coronary sinus and venous reservoir after the two moments of reperfusion (B1/B2 and CS1/CS2) were higher when CS2 (P<0.05). Despite higher values ​​after the end of cardiopulmonary bypass (A2), when compared to samples of anesthesia (A1), those show a downward trend when compared to the samples of the second moment of reperfusion (CS2) (P<0.05). Conclusion: The measurement of malondialdehyde shows that coronary artery bypass grafting with cardiopulmonary bypass is accompanied by increase of free radicals and this trend gradually decreases after its completion. Aortic clamping exacerbates oxidative stress but has sharper decline after reperfusion when compared to systemic metabolism. The behavior of thiobarbituric acid species indicates that oxidative stress is an inevitable pathophysiological component.